Anatolian Pottery as a Basis for Cultural Syntheses (Anatolia and Mesopotamia – Anatolia and her Southern Neighbors – Anatolia and Southeastern Europe – Ceramic Changes in Anatolia – Pottery Cycles – The Use of Pottery in Field Surveys) - Mellaart, James
published by the Wenner-Gren Foundation for Anthropological Research, Inc. (= Viking Fund Publications in Anthropology, edited by Sol Tax, vol. 41. London 1966. Methuen and Co.).